Hubungan Perilaku Bullying Dengan Konsep Diri Pada Anak Di SDIT Al-Uswah Tuban - Haepy Azelia Zahra; Fadila Rizki Amalia; Dadang Kusbiantoro; Sylvi Harmiardillah (EduInovasi: Journal of Basic Educational Studies, 2024)
Self-concept is an individual's views and feelings about himself that determine the determinants in communicatingwith others. Children who have a negative self-concept will view themselves and their environment in a low lightand aggressiveness among students will have the most negative impact. The purpose of this study was to determine the relationship between bullying behavior and self- concept in children at SDIT Al-Uswah Tuban. The design of this study used analytic correlation with a cross-sectional approach which was analyzed using random sampling technique on 52 respondents. The data was taken using a questionnaire on bullying behavior and self-concept, thenanalyzed using the Spearman rank test. The results showed that 71.2% had a high self-concept, 69.2% had mild bullying behavior. Statistical test results obtained p = 0.001 (p <0.05) and r = 0,436, which means that there is a significant relationship between bullying behavior and self-concept in children with sufficient relationship strength.Students who have a high self- concept have low bullying behavior. Therefore, parents are expected to monitor andgive advice to their children to be kind to others. Therefore, the school teaches children many things so that this can become a child's weapon in the future through religious knowledge, because to become a better person.